2004
DOI: 10.1002/jccs.200400190
|View full text |Cite
|
Sign up to set email alerts
|

A New Synthesis of Benzofurans from Phenols via Claisen Rearrangement and Ring‐Closing Metathesis

Abstract: Based on Claisen rearrangement, the double bond isomerization of O-allyl function together with the formation of O-vinyl function in one pot, and ring-closing metathesis (RCM), various phenols were transformed into various benzofurans in good yields. these allyl aryl ethers (2a-f) were heated to reflux in decalin to undergo Claisen rearrangement to produce O-allyl phenols (3a-h) in 80-87% yields, respectively. Compound 2e or 2f, which is the same compound, gave compound 3e, orthoproduct, and para-product 3f in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 31 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…In another example from the van Otterlo group, a “double” isomerization strategy on the bis-allyl substrates 577 readily afforded compounds 578 , in which, most interestingly, both the O - and the C -allyl groups were isomerized as illustrated in Scheme . These compounds were then facilely converted into their respective substituted benzofurans 579 by RCM, in generally acceptable yields. ,, A related approach was employed by Wang and co-workers, with the difference being that they generated the substituted benzofurans from bisalkenes, which in turn were generated by potassium butoxide-mediated isomerization and elimination reactions as also shown in Scheme . , The Wang group transformed ethers 580 into the conjugated ethers 581 followed by RCM with the Grubbs first generation catalyst GI using an essentially similar approach to afford their benzofurans and applied this strategy in their further work on substituted coumarins , and 2,5-dihydro­[ b ]­oxepines (not illustrated).…”
Section: Transition Metal-mediated Isomerizations Of Allylbenzenesmentioning
confidence: 99%
See 1 more Smart Citation
“…In another example from the van Otterlo group, a “double” isomerization strategy on the bis-allyl substrates 577 readily afforded compounds 578 , in which, most interestingly, both the O - and the C -allyl groups were isomerized as illustrated in Scheme . These compounds were then facilely converted into their respective substituted benzofurans 579 by RCM, in generally acceptable yields. ,, A related approach was employed by Wang and co-workers, with the difference being that they generated the substituted benzofurans from bisalkenes, which in turn were generated by potassium butoxide-mediated isomerization and elimination reactions as also shown in Scheme . , The Wang group transformed ethers 580 into the conjugated ethers 581 followed by RCM with the Grubbs first generation catalyst GI using an essentially similar approach to afford their benzofurans and applied this strategy in their further work on substituted coumarins , and 2,5-dihydro­[ b ]­oxepines (not illustrated).…”
Section: Transition Metal-mediated Isomerizations Of Allylbenzenesmentioning
confidence: 99%
“…320,733,736 A related approach was employed by Wang and co-workers, with the difference being that they generated the substituted benzofurans from bisalkenes, which in turn were generated by potassium butoxide-mediated isomerization and elimination reactions as also shown in Scheme 150. 737,738 The Wang group transformed ethers 580 into the conjugated ethers 581 followed by RCM with the Grubbs first generation catalyst GI using an essentially similar approach to afford their benzofurans and applied this strategy in their further work on substituted coumarins 739,740 and 2,5-dihydro[b]oxepines 741 (not illustrated). The strategy used by the van Otterlo group was amended to afford nitrogen-containing annulated compounds, albeit with less success.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…Unfortunately, the direct arylation reaction did not take place and only product 15 derived from competing Mizoroki-Heck coupling was found, instead. Hence, the alternative approach using 5-chlorobenzo[b]furan 17 as starting material was investigated (Scheme 2) [24,28]. In our previous publication [10], it was observed that aryl chlorides were unreactive as coupling partners under the reaction conditions and, hence, homo-coupling of the benzofuran starting material should not be an issue.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous publication [10], it was observed that aryl chlorides were unreactive as coupling partners under the reaction conditions and, hence, homo-coupling of the benzofuran starting material should not be an issue. Hence, the alternative approach using 5-chlorobenzo[b]furan 17 as starting material was investigated (Scheme 2) [24,28]. In our previous publication [10], it was observed that aryl chlorides were unreactive as coupling partners under the reaction conditions and, hence, homo-coupling of the benzofuran starting material should not be an issue.…”
Section: Resultsmentioning
confidence: 99%